سمات الشخصية لأيزنك وعلاقتها بالمجهدين العاملين بمناصب التعامل مع الجمهور - بن معزوزة خديجة (My University, 2018)
The study aimed to identify personality traits according to the standard of Ayznek (EPQ) personality (neurotic, diastolic, psychotic and lying). The investigation was based on a sample of municipal employees working in the Civil Affairs Department who deal directly with the different public groups. At the same time, the study aimed at identifying the relationship between Personality traits and stress levels under certain personal variables such as sex, age, professional experience and scientific level. The sample of the actual study consisted of -140- employees of the civil status department; among which 70 were males and ) ( were females. The sample was not chosen at random but it two tools of research such as the Ayznek personality profile modified and translated by Ahmed Abdel Khalek (1991), and a neurological stress questionnaire. As far as this research is concerned, were used, including Pearson correlation coefficient and binary variance -------------- ------------ ---------------The study showed the following results: ----------------------------------------------------------------------------- -------- ------- --------------------------------------------------------------------------------------- The most common feature of personality (neurotic, diastolic, psychotic, and lying) among employees in the positions of interaction with the public is attributed to the trait of lying (social desirability). -sex, age - professional experience and scientific level(. While there were psychotic, lying) and due to the variable of scientific level among the employees in the interaction with the public.  There are no statistically significant differences in personality traits (diastolic, psychosis, and lying) among people in public interaction positions due to stress levels (high, medium, low). While there were statistically significant differences in the trait characteristic of the employees in the interaction with the public due to the levels of stress (high, medium, low).  There are no statistically significant differences in stress due to )sex , age variables, professional experience and scientific level( among employees in interaction with the public.